Ministry of Tourism Decree No. 661 of the Year 2016 Issued on 21/7/2016 = وزارة السياحة قرار رقم 661 لسنة 2016 صادر بتاريخ 21-7-2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic